2020
DOI: 10.1186/s12884-020-03251-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of family resources on secondhand smoking in pregnant women: a cross-sectional study in the border and minority urban areas of Northwest China

Abstract: Background Pregnant women’s exposure to secondhand smoke is a very serious health issue in China. The purpose of our research is to identify factors that predict the probability of exposure to secondhand smoke among pregnant women from the perspective of a family-based open system. Methods From September 2014 to August 2015, Urumqi City, Shihezi City, and Shawan County-level City were sampled according to population characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In addition, the age of pregnant women was also considered an indicator for predicting SHS exposure during pregnancy, and it was positively associated with SHS exposure [29,31,32]. The accumulation hypothesis showed that the level of SES-based health advantages progressively declined with age [33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the age of pregnant women was also considered an indicator for predicting SHS exposure during pregnancy, and it was positively associated with SHS exposure [29,31,32]. The accumulation hypothesis showed that the level of SES-based health advantages progressively declined with age [33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies conducted in countries where the patriarchal family structure is dominant show that home is where the woman can spend time with her husband freely and women want their husbands to be with them at home. Therefore, the rate of PECS increases during pregnancy [20,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, family's consensus on smoking ban may be an effective strategy [23], as in the pregnancy women are well protected in family, particularly their spouse/partner value their advice. In a word, it is imperative for both pregnant women and their spouse/partner to be included in interventions for tobacco control and ongoing implementation of preconception and pregnancy health education.…”
Section: Discussionmentioning
confidence: 99%
“…In additional, pregnant women's age was also considered as another indicator to predict the SHS exposure during pregnancy and it was positive associated with SHS exposure [21,23,24]. The accumulation hypothesis showed the level of SES-based health advantage progressively decline as age [25].…”
Section: Introductionmentioning
confidence: 99%